Interleukin-7 and Anti–Programmed Cell Death 1 Antibody Have Differing Effects to Reverse Sepsis-Induced Immunosuppression. Issue 4 (April 2015) - Shindo, Yuichiro; Unsinger, Jacqueline; Burnham, Cary-Ann; Green, Jonathan M.; Hotchkiss, Richard S.
<x xml:space="preserve">Abstract</x> ABSTRACT Sepsis remains a major cause of morbidity and mortality in most intensive care units. Protracted sepsis can evolve into a state of profound immunosuppression characterized by secondary infections, frequently with opportunistic-type pathogens. Immunoadjuvant therapy is currently being evaluated as a novel treatment for patients with sepsis. Two of the most promising immunoadjuvants are interleukin-7 (IL-7) and anti–programmed cell death 1 antibody (anti–PD-1). Both IL-7 and anti–PD-1 have been reported to boost host immunity and improve outcomes in patients with viral infections and cancer. The purpose of this study was to define the immunological mechanisms of action of IL-7 and anti–PD-1 in the two-hit sepsis model of cecal ligation and puncture followed by Candida albicans. In addition, we examined whether combined treatment with IL-7 and anti–PD-1 provided any additive beneficial effects in reversing immune dysfunction. The present findings demonstrated that IL-7 and anti–PD-1 had differing effects on innate and adaptive immune functions. Compared with anti–PD-1, IL-7 increased lymphocyte proliferation; expression of lymphocyte adhesion molecules, lymphocyte function–associated antigen 1, and very late antigen-4; interferon-γ production; and CD28 expression on splenic CD8+ T cells. In contrast, anti–PD-1 seemed to have a greater effect on major histocompatibility complex class II expression on splenic macrophages and dendritic cells than IL-7. Combined treatment with IL-7 and anti–PD-1 produced additive effects on CD28 expression, lymphocyte proliferation, and splenic secretion of interferon-γ. In conclusion, the present study shows differences in immunomodulatory actions between IL-7 and anti–PD-1 and provides a potential rationale for combining IL-7 and anti–PD-1 in the therapy of sepsis.